Research on Electromagnetic Excitation Resonant Sensor Based on Microelectromechanical System - Gang Li; Xiaofeng Zhao; Dianzhong Wen; Yang Yu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In this paper, an electromagnetic excitation resonant sensor was designed based on Microelectromechanical system (MEMS) technology. In this new sensor, four nc-Si/c-Si heterojunction p-MOSFETs are manufactured by using the technique of MEMS on the N-type orientation high resistance silicon wafer, and a Wheatstone bridge is composed of four nc-Si/c-Si heterojunction MOSFETs channel resistances, output voltage of the bridge circuit changes according to the applied pressure. A vibration will be generated when an alternating current is applied to the inductance coil of electromagnetic excitation resonant sensor, the maximum power produced in the central part of the four edges of silicon membrane, whose frequency and amplitude are associated with the current in the inductance coil, and the applied pressure P can be detected. Using mechanics and electromagnetism coupling field analysis by Ansys software, the simulation to vibration situation of the silicon membrane of sensor was carried on when vertical magnetic field and alternating current were loaded. Experimental results show that, as the operating voltage is constant, with the increase of current in the inductance coil the conversion of applied pressure increases, and the output voltage of nc-Si/c-Si heterojunction MOSFETs pressure sensor is proportional to the increase of coil magnetic field i.e. the increase of pressure, the experimental results are consistent with the simulation results.